2021
DOI: 10.1186/s12876-021-01975-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sampling methods in assessing the microbiome from patients with ulcerative colitis

Abstract: Background Dysbiosis of ulcerative colitis (UC) has been frequently investigated using readily accessible stool samples. However, stool samples might insufficiently represent the mucosa-associated microbiome status. We hypothesized that luminal contents including loosely adherent luminal bacteria after bowel preparation may be suitable for diagnosing the dysbiosis of UC. Methods This study included 16 patients with UC (9 men and 7 women, mean age: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Most microbiome and GI cancer studies have focused on the microbiome analysis in fecal samples [1,29], which is a convenient and non-invasive approximation of the patient intestinal microbial biodiversity. However, it is well known that fecal samples do not represent the microbial communities of colon tissues [30,31]. In addition, last year's works support the correlation between oral and tumor microbiota [3,26,27,29,32], underlining that further microbiome analyses of oral uids and colon mucosa tissues in CRC patients are needed in order to study the potential role of anaerobe oral pathobionts in initiation and/or aggravation of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Most microbiome and GI cancer studies have focused on the microbiome analysis in fecal samples [1,29], which is a convenient and non-invasive approximation of the patient intestinal microbial biodiversity. However, it is well known that fecal samples do not represent the microbial communities of colon tissues [30,31]. In addition, last year's works support the correlation between oral and tumor microbiota [3,26,27,29,32], underlining that further microbiome analyses of oral uids and colon mucosa tissues in CRC patients are needed in order to study the potential role of anaerobe oral pathobionts in initiation and/or aggravation of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…2B ). It is commonly observed that LAM and MAM exhibit differences in their composition 14,35,36 . For instance, Miyauchi et al 14 conducted a comparative analysis between LAM derived from feces and MAM samples collected by swabbing the mucosa in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…While we used fecal calprotectin as a measure of intestinal inflammation, evaluating histological markers that are elevated in IBS patients such as mast cells would allow for a more accurate measure of inflammation including by location in the GI tract and types of inflammation 48 . Similarly, given potential differences in the microbiome between direct luminal sampling and stool samples, direct sampling during endoscopy may provide a better representation of the relationship between our IBS measures and the microbiome 49,50 . Other future directions could include investigating the potential link between metabolic pathways with the gut–brain axis and neuromodulation and the inclusion of metabolomic analysis.…”
Section: Discussionmentioning
confidence: 99%